Population aging and its implications to marketing management: an investigation in the sector of gym academies - Queiroz, Renata S. Bernardes; Serra, Marcia Milena Pivatto; Orsi, Emília; Mazzieri, Marcos Rogério (Revista de Administração da UFSM, 2018)
This work aims at analysing how gym academies are responding to the phenomenon of population ageing. Some research and studies have already pointed out specific needs of the elderly segment. However, this work intends to discuss the aging market and the supply of sports services and academies for individuals over 40 years old (the aging segment), who start to present physical needs and limitations associated with the aging process. The research approach is qualitative descriptive and the data was obtained through interviews with owners or staff of academies located in the metropolitan region of Campinas. The analysis of the results indicated the recognition of the potential of senior and mature consumers (between 40-59 years old). However none of the respondents had practices and services that exclusively met the needs of this group of consumers. In this context, the research sought to identify the factors and attributes most relevant to the supply of services of academies to the aging public, based on the recognition of the opportunity and the potential posed by this market. The study presents some contribution to the area of marketing services, as also adds relevant aspects to the development of businesses that seek this potential market.